Association of multiple sclerosis and sudden sensorineural hearing loss. (31st May 2016) - Atula, S; Sinkkonen, ST; Saat, R; Sairanen, T; Atula, T
Background: Multiple sclerosis (MS) may affect other cranial nerves besides the optic nerve. Sudden sensorineural hearing loss (SSHL), possibly caused by a deficit in the auditory tract, including the vestibulocochlear nerve, is sometimes associated with MS. Objectives: We aimed to assess the incidence of SSHL among MS patients, its frequency as an initial symptom of MS, and magnetic resonance imaging (MRI) findings associated with SSHL in MS. Methods: We collected retrospectively all patients diagnosed with MS and SSHL at the Helsinki University Hospital between 2004 and 2014. Patients with both diagnoses were re-evaluated using hospital medical records, audiograms and head MRI scans. Results: A total of 2736 patients were diagnosed with MS, 1581 patients with SSHL, and 18 patients (0.7% of all MS patients) with both; two patients presented with SSHL as an initial symptom of MS. The annual incidence of SSHL was 59.8/100 000 (95% confidence interval (CI) 37.7–94.9) in MS patients, and 12.4/100 000 (95% CI 11.8–13.0) in the normal population. Conclusion: SSHL is a rare symptom of MS and is even less frequent as an initial symptom. Its incidence in MS patients, however, markedly exceeds that in the normal population.